Late results of right ventricular outflow tract reconstruction with Björk-Shiley valved conduits. Issue 4 (April 1986) - Meldrum-Hanna, W; Cartmill, T; Johnson, D; Celermajer, J; Hawker, R
Abstract : Between 1971 and December 1976, 27 children with congenital heart disease underwent right ventricular outflow tract reconstruction with conduits incorporating a Björk-Shiley valve. The conditions corrected were pulmonary atresia with ventricular septal defect (14 patients), truncus arteriosus (6 patients), and complex disease (7 patients). At operation the children were aged from 12 days to 16 years (five patients were less than one year old). Overall mortality for the group was high (52%). There were nine early deaths and five late ones. Actuarial survival till death or reoperation was 55% at four years, 35% at eight years, and 28% at 12 years. Ten children subsequently underwent reoperation for conduit stenosis caused by neointimal proliferation and valve obstruction. The new conduits incorporated a biological valve. Mortality was highest in patients aged less than one year, and in those with truncus arteriosus, severe pulmonary hypertension, or complex heart disease. Mechanical valves should be avoided in conduit reconstruction of the right ventricular outflow tract for congenital heart disease.